Pendidikan Kesehatan tentang Upaya Penanganan Mandiri Dismenorea Di SMP Negeri 16 Kota Jambi - Marnila Yesni; Dwi Kartika Febrianti; Dwi Yunita Ramadhani; Yuliana Yuliana; Rahmi Dwi Yanti (Jurnal Abdimas Kesehatan (JAK), 2023)
Dysmenorrhea is the main gynecological problem that is most often complained of by adolescents, and the most common is primary Dysmenorrhea. Junior high school is the period when teenagers begin to adapt to the menstruation they experience, they need more knowledge related to this. The problem of menstrual disorders is the first largest order in Jambi City with a total of 1143 adolescents experiencing menstrual disorders and the Rawasari Health Center Work Area with the highest number of 258 cases. SMP N16 is a state junior high school located in the Rawasari Health Center working area, based on a survey of 5 dominant SMP N 16 students who said that almost every month they experience Dysmenorrhea, this can affect student learning processes, reduce learning concentration and of course will affect student achievement, in dealing with it they only consume pain relievers. This requires independent treatment to minimize the use of pharmacological drugs. Therefore, early adolescents need information and socialization regarding independent handling when they experience Dysmenorrhea. This community service was carried out on 20 female students using the lecture method and video playback, the material provided was about Dysmenorrhea and some self-management with compresses and steps to use several herbs to relieve Dysmenorrhea. After community service from the results of the evaluation by distributing pre and post questionnaires, it was found that the average knowledge of female students was 3.7 about Dysmenorrhea and independent handling of Dysmenorrhea. This community service can provide benefits for students in overcoming Dysmenorrhea and it is hoped that the UKS can socialize it to other students